Implementasi Pemikiran Zakiah Daradjat Dalam Menghadapi Isu Kesehatan Mental di Institusi Pendidikan Islam - Bahri, A.Saeful; Napsin, Napsin; Maryati, Nenden; Jamilah, Rd. Elih (Penerbit Widina, Widina Media Utama, 2024)
This Research purpose to observe the implementation of Prof. Zakiah Daradjat's thoughts in Islamic educational institutions to deal with mental disorders that occur in adolescents. By using descriptive analysis on books and translated works as primary sources, and applying interview techniques with teachers and observation techniques on cases at the Ruhama Islamic Educational Institution, under the auspices of Prof. Dr. Zakiah Daradjat Jakarta Foundation. Zakiah's thoughts on mental health and Islamic religious psychology are applied to the institution of religious studies colleges (PTK). Educational management in this Islamic educational institution focuses on guidance and counseling on mental health by applying the concept of Islamic religious psychology that can be applied to students at elementary, middle and Islamic higher education institutions.ABSTRAKPenelitian ini bertujuan untuk melihat implementasi pemikiran Prof. Zakiah Daradjat di intitusi Pendidikan islam untuk menangani gangguan mental yang terjadi pada remaja. Dengan menggunakan analisis deskriptif pada buku-buku dan karya-karya terjemahan sebagai sumber primer, dan menerapkan teknik wawancara dengan guru serta teknik observasi pada kasus yang ada di Lembaga Pendidikan Islam Ruhama, di bawah naungan Prof. Dr. Zakiah Daradjat Yayasan Jakarta. Pemikiran Zakiah dalam Kesehatan mental dan psikologi agama islam di terapkan pada institusi sekolah tinggi studi Keagamaan (PTK). Manajemen Pendidikan di intitusi Pendidikan Islam ini berfokus pada bimbingan dan konseling terhadap Kesehatan mental dengan penerapan konsep psikologi agama islam yang dapat diterapkan kepada siswa ditingkat SD, menengah hingga di lembaga Pendidikan tinggi islam.